2022
DOI: 10.1128/spectrum.01816-22
|View full text |Cite
|
Sign up to set email alerts
|

Class A Penicillin-Binding Protein C Is Responsible for Stress Response by Regulation of Peptidoglycan Assembly in Clavibacter michiganensis

Abstract: Peptidoglycan of cell walls in bacteria is a cross-linked and meshlike scaffold that provides strength to withstand the external pressure. The increased cross-linkage in peptidoglycan and altered structure in VBNC cells endowed the cell wall more resistant to adversities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Regarding cell morphology, the △ pbpC mutants were not rod-shaped but instead had a thinner cell wall, as observed by transmission electron microscopy and atomic force microscopy. The △ pbpC mutants of C. michiganensis strain BT0505 were more sensitive to lysozymes and environmental stress response, such as ultrasonication and Cu 2+ treatment [ 17 , 48 ]. However, the mechanism of these phenotypic changes in the △ pbpC mutants associated with their increased virulence in tomato seedlings was firstly demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding cell morphology, the △ pbpC mutants were not rod-shaped but instead had a thinner cell wall, as observed by transmission electron microscopy and atomic force microscopy. The △ pbpC mutants of C. michiganensis strain BT0505 were more sensitive to lysozymes and environmental stress response, such as ultrasonication and Cu 2+ treatment [ 17 , 48 ]. However, the mechanism of these phenotypic changes in the △ pbpC mutants associated with their increased virulence in tomato seedlings was firstly demonstrated in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Two strains of C. michiganensis GS12102 and BT0505, which differ in their geographic origin and plasmid number, were used to prepare △ pbpC mutants and a series of derived strains. It was revealed that the thickness of the cell wall peptidoglycan layer of strain BT0505 △ pbpC mutants is thinner and the number of cross-links is decreased compared with those of the wild-type strain [ 48 ]. Accordingly, a lack of pbpC in C. michiganensis appeared to result in a more fragile cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…PBPs are classified into two main categories based on their molecular weight: high-molecular-weight (HMW) PBPs and low-molecular-weight (LMW) PBPs [14]. Class A PBPs are HMW PBPs with molecular weights typically exceeding 100 kDa [15]. They are responsible for crosslinking peptidoglycans in the cell wall and exhibit both transglycosylase and transpeptidase activities [16].…”
Section: Introductionmentioning
confidence: 99%